Genetic stock identification of immature chum salmon (Oncorhynchus keta) in the western Bering Sea, 2004 - Kang, Minho; Kim, Suam; Low, Loh-Lee (Ocean science journal, 2016)
Genetic stock identification studies have been widely applied to Pacific salmon species to estimate stock composition of complex mixed-stock fisheries. In a September-October 2004 survey, 739 chum salmon ( Oncorhynchus ket a) specimens were collected from 23 stations in the western Bering Sea. We determined the genetic stock composition of immature chum salmon based on the previous mitochondria DNA baseline. Each regional estimate was computed based on the conditional maximum likelihood method using 1,000 bootstrap resampling and then pooled to the major regional groups: Korea - Japan - Primorie (KJP) / Russia (RU) / Northwest Alaska (NWA) / Alaska Peninsula - Southcentral Alaska - Southeast Alaska - British Columbia - Washington (ONA). The stock composition of immature chum salmon in the western Bering Sea was a mix of 0.424 KJP, 0.421 RU, 0.116 NWA, and 0.039 ONA stocks. During the study period, the contribution of Asian chum salmon stocks gradually changed from RU to KJP stock. In addition, North American populations from NWA and ONA were small but present near the vicinity of the Russian coast and the Commander Islands, suggesting that the study areas in the western Bering Sea were an important migration route for Pacific chum salmon originating both from Asia and North America during the months of September and October. These results make it possible to better understand the chum salmon stock composition of the mixed-stock fisheries in the western Bering Sea and the stock-specific distribution pattern of chum salmon on the high-seas.